WAJAH AGAMA HINDU DI ZAMAN KALI YUGA - Putu Dana Yasa Putu Dana Yasa (UHN IGB Sugriwa Denpasar, 2022)
Hinduism has always been synonymous with peace and harmony throughout its civilization, but lately due to various factors, this condition has been eroded if you look at the quality of religious people, especially the Hindu environment. Various problems arise among Hindus in the midst of the current Kali Yuga era, ranging from religious debates, the emergence of truth claims, endless religious conflicts, until the politicization of religion becomes an appearance and even an open spectacle for anyone. This is of course due to the lack of literacy or religious understanding within Hinduism and is also connected to the negative impact of technological developments that make it easy for anyone to express opinions, especially in various social media networks. If this continues, the peaceful face of Hinduism will only collapse and be buried in such a deep pit. Hinduism with theological teachings that are anandi-ananta (no beginning and no end) should be able to survive in this yuga era, because Hinduism can always be adapted to the times, but sometimes due to the rigid thinking of its followers, Hinduism has so many religious problems.